Usefulness of Skin Autofluorescence as a Biomarker of Acute Oxidative Stress in Young Male Japanese Long-Distance Runners: A Cross-Sectional Study - Rei Fujiwara; Natsume Anzai; Motoyasu Ishikawa; Atsuhiko Takahashi (MDPI AG, 2022)
Chronic oxidative stress in long-distance runners adversely affects conditioning. It is important to objectively assess and monitor oxidative stress, but measuring oxidative stress can be invasive or require skill to measure. Therefore, this study aimed to verify whether skin autofluorescence (SAF), a non-invasive, rapid, and easily calculable metric for calculating advanced glycation end products (AGEs), is useful as an oxidative stress biomarker. The subjects were 50 young Japanese male long-distance runners (aged 20.2 ± 1.2 years); 35 average-sized male university students (aged 19.8 ± 1.1 years) served as controls. The interactions and relationships between SAF and plasma pentosidine and oxidative stress markers (reactive oxygen metabolite-derived compounds [d-ROMs], biological antioxidant potential [BAP], and the BAP/d-ROMs ratio) in runners were examined, and SAF in the runners and controls was compared. The results suggest that plasma pentosidine in runners is associated with oxidative stress markers and that it can assess oxidative stress. However, as SAF was not associated with oxidative stress markers, it was not validated as one. In future, clarifying the factors affecting SAF may also clarify the relationship between SAF, plasma pentosidine, and oxidative stress markers.